Analysis Of The Influence Of Perceived Usefulness, Subjective Norm And Perceived Ease Of Use On Usage Behavior Through Behavioral Intention On The Acceptance Of Rme In Rsud Mayjend H.M. Ryacudu North Lampung - Febrian Pramana Putra; Agusdini Agusdini; Nofierni Nofierni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
In the era of digital transformation, the healthcare sector is required to adapt to technological developments, especially in terms of recording and managing patient medical data. Electronic Medical Records (RME) is a strategic solution that can improve efficiency, accuracy, and integration of health services. The implementation of RME in health facilities faces a number of challenges. Infrastructure readiness, limited human resources (HR), and resistance to change are factors that affect the adoption of this technology. to analyze the extent to which Perceived Usefulness, Subjective Norm and Perceived Ease of Use affect Usage Behaviour through Behavioural Intention as an intervening variable. this research method is quantitative explanatory research. The sample in this study were care givers (PPA) at the Mayjend H.M. Ryacudu Hospital, North Lampung, totaling 140 respondents. Data collection using questionnaires and descriptive analysis techniques using the SEM-PLS method. the results showed Perceived Usefulness, Subjective Norm and Perceived Ease of Use influence directly and indirectly on Usage Behaviour through Behavioural Intention as an intervening variable on the acceptance of RME at Mayjend H.M. Ryacudu Hospital. These results in theoretical implications support the theory and previous research. Managerially, it is expected to provide input for the management of RSUD Mayjend H.M. Ryacudu to understand the factors that influence the acceptance of RME by medical personnel, so that technology adoption strategies can be more effective, in improving and improving the quality of technology and systems that support the use of RME.